Studi Evaluatif Terhadap Interpretasi Kaum Revisionis Tentang Homoseksualitas Berdasarkan Roma 1:26-27 - Tembang, Setblon; Tanyid, Maidiantius; Wilayanto, Wilayanto (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
This research is motivated by differences in views between revisionists and traditional understanding of the interpretation of Romans 1:26-27. The text in Romans 1:26-27 is traditionally considered and accepted as a text prohibiting even condemning LGBTIQ practices. However, the revisionists view that the acts condemned in Romans 1:26-27 do not refer to people with a homosexual orientation, but homosexuals committed by heterosexual people. This study aims to review the Bible's teaching on LGBTIQ to evaluate the revisionist interpretation of Romans 1:26-27. The approach in this research is qualitative research using hermeneutic methods and literature review. In the view of the revisionists, Romans 1: 26-27 discusses criticism of idol worship, criticism of heterosexuals, not homosexuals, discusses relationships that are unequal and driven by excessive lust. But looking back at Romans 1:26-27, LGBTIQ is a sin that violates God's law and not just as a punishment for idol worship. Paulus views LGBTIQ as a sin and deserves to receive the appropriate punishment for his mistakes. So, based on these findings, the revisionists were more influenced by presuppositions in reinterpreting Romans 1:26-27.